Protective coating and protective treatment method for turnover template
By spraying protective coatings of nano alumina and other components on the surface of the 3D printed template, a dense film structure is formed, which solves the bonding problem of the template during demolding, and realizes the turnaround use and hardness improvement of the template. It is suitable for many types of template.
Patent Information
- Application Number
- CN202411329249.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-09-24
AI Technical Summary
It is difficult to achieve turnaround utilization of 3D printed templates, and the existing turnaroundable templates are prone to bond when demolded, resulting in damage and reduced use times.
Provide a protective coating that can turn over the template, including nano-alumina, nano-silicon carbide powder, rare earth oxides, epoxy resin and other components. By spraying on the surface of the template, it forms a dense film structure to reduce adhesion and increase hardness, ensuring The template will not be damaged during demolding.
The turnaround use of 3D printed templates is realized, reducing the damage to the template during transportation and demolding, increasing the turnaround times of the template, and suitable for other types of templates such as wooden templates and plastic templates.
Smart Images

Figure CN119144208A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building concrete, and more specifically to a protective coating for a turnaround formwork and a protective treatment method. Background Art
[0002] With the improvement of people's living standards, people require that buildings, while meeting their functional requirements, increasingly pursue their artistic sense and aesthetics. The application of complex shapes in buildings will become more and more extensive. There are many shapes and types of complex shapes, such as special-shaped columns (variable section columns, curved columns, etc.), special-shaped beams (curved beams, variable section beams, etc.), special-shaped panels (curved panels, honeycomb panels, etc.). For these special-shaped structures, there are currently two common implementation plans. One is to directly print special-shaped structures based on 3D printing technology. This solution is easier to achieve special-shaped and decorative effects. However, in practice, due to the existence of weak bonding interfaces between layers, the printed templates are not suitable for load-bearing components, and it is difficult to demold and cannot be used in circulation. The second solution is to use special recyclable combined templates. At present, the common recyclable special-shaped templates are mostly wooden templates, steel templates and plastic templates. The advantages of these templates are easy demoulding, high surface flatness, and simple special shapes can be achieved, but the process of making finishing effects is complicated, the cost is high, and the decorative effect is poor. How to use 3D printing technology to achieve the turnover of templates is of great significance.
[0003] The patent with publication number CN117645824A discloses a coating for the surface of 3D printed parts. The coating is based on epoxy resin and talcum powder, combined with auxiliary preparations such as silica and calcium carbonate, to obtain a liquid coating suitable for the surface treatment of 3D printed parts. After the coating is applied and solidified on the printed part, it can effectively cover the upper layer of the printed part, and at the same time play the role of smoothing the parts and improving the mechanical properties and weather resistance of the printed parts. However, the coating is difficult to achieve the recycling of 3D printed templates. Concrete needs to be poured inside the template when it is used. If the 3D printed template is difficult to demold, it still cannot be recycled. Summary of the invention
[0004] 1. Technical problem to be solved by the invention
[0005] In view of the fact that 3D printed templates in the prior art are difficult to be recycled, the present invention intends to provide a protective coating and a protective treatment method for recyclable templates. By spraying the protective coating on the surface of the 3D printed template, it helps to prevent the template and the cast-in-place wall from sticking together during demolding, and it is not easy to damage the template and the wall, thereby achieving the recyclable recycling of the 3D printed template. The protective coating and treatment method can also be applied to other types of templates such as wooden templates, plastic templates, etc., which helps to further improve their turnover performance.
[0006] 2. Technical solution
[0007] In order to achieve the above object, the technical solution provided by the present invention is:
[0008] The protective coating of the turnable template of the present invention comprises the following components in parts by weight:
[0009] Nano-alumina: 18-26 parts by mass, in practice, 18 parts by mass, 20 parts by mass, 25 parts by mass, 26 parts by mass, etc. can be used;
[0010] Nano silicon carbide powder: 13-21 parts by mass, in practice, 13 parts by mass, 15 parts by mass, 18 parts by mass, 21 parts by mass, etc. can be used;
[0011] Rare earth oxide: 1-3 parts by mass, which can be 1 part by mass, 2 parts by mass, 3 parts by mass, etc. in practice;
[0012] Epoxy resin: 58-65 parts by weight, in practice, 58 parts by weight, 60 parts by weight, 63 parts by weight, 65 parts by weight, etc. can be used;
[0013] Dispersant: 0.5-0.9 parts by mass, in practice, 0.5 parts by mass, 0.6 parts by mass, 0.7 parts by mass, 0.9 parts by mass, etc. can be used;
[0014] Polyether polyol: 70-75 parts by mass, in practice, 70 parts by mass, 72 parts by mass, 73 parts by mass, 75 parts by mass, etc. can be used;
[0015] Micro powder: 5-7 parts by mass, in practice, 5 parts by mass, 6 parts by mass, 6.5 parts by mass, 7 parts by mass, etc. can be used;
[0016] Plasticizer: 2-5 parts by weight, in practice, 2 parts by weight, 3 parts by weight, 4 parts by weight, 5 parts by weight, etc. can be used;
[0017] Curing agent: 0.9-1.6 parts by mass, which can be 0.9 parts by mass, 1.0 parts by mass, 1.5 parts by mass, 1.6 parts by mass, etc. in practice;
[0018] Coagulant: 2-3 parts by mass, in practice, 2 parts by mass, 2.3 parts by mass, 2.5 parts by mass, 3 parts by mass, etc. can be used;
[0019] Additives: 8-12 parts by mass. In practice, 8 parts by mass, 10 parts by mass, 11 parts by mass, 12 parts by mass, etc. can be used.
[0020] Furthermore, the rare earth oxide is Er2O3; or / and, the dispersant is sodium polyacrylate; or / and, the plasticizer is ditolyl phosphate; or / and, the curing agent is ethylenetriamine; or / and, the coagulant is calcium aluminate; or / and, the additive is non-tar asphalt.
[0021] Furthermore, the average particle size of nano-alumina is 60-70 nm; or / and the average particle size of nano-silicon carbide is 45-55 nm; or / and the density of epoxy resin is 1.1-1.3 g / cm 3 , viscosity is 7500-8000 Pa·s; or / and, the micropowder is silicon carbide powder, the average particle size of the micropowder is 25-30 nm, and the specific surface area is 80-100 m 2 / g, density is 3.6~3.9g / cm 3 .
[0022] The present invention also provides a protective treatment method for a turnaround template, which comprises spraying the protective coating as described above on the surface of the template.
[0023] Furthermore, the following processes are included:
[0024] S1. After the template is made, the template surface is cleaned and a layer of water-based primer is applied on the template surface;
[0025] S2. Spray protective coating on the template surface.
[0026] Furthermore, in step S2, carboxymethyl cellulose is added as a viscosity regulator when spraying the protective coating, and the amount of carboxymethyl cellulose is 2.5-3% of the total weight of the coating, and in practice, 2.5%, 2.8%, 3%, etc. can be used.
[0027] Furthermore, the protective coating in step S2 is sprayed no less than three times, such as three to five times, with an interval of no less than 3 hours, such as an interval of 3 to 4 hours between two sprayings, and the thickness of each spraying is not less than 0.03 mm, such as the thickness of each spraying is 0.03-0.05 mm, etc.
[0028] Furthermore, in step S1, after the template is completed, the edges of the vertical strips on the inner side of the template are cut to form a wedge-shaped protrusion on the inner side, and then the surface of the template is cleaned.
[0029] Furthermore, in step S1, after the water-based primer is applied to the surface of the template, the surface of the template is roughened and then the protective coating is sprayed.
[0030] Furthermore, after the spraying of step S2 is completed, the lubricating isolation layer is continuously brushed on the surface of the template, that is, after the interface layer is formed, before the wall is poured, the interface layer on the inner surface of the template is evenly brushed with engine oil, and the engine oil completely covers the interface layer.
[0031] It should be noted that the surface treatment technology of the template is one of the challenges faced in the production of 3D printed turnaround templates. The commonly used template demolding method in the industry is to apply a release agent on the template surface. The types of release agents include pure oil release agents, emulsified oil release agents, saponified oil release agents, paraffin release agents, chemically active release agents, synthetic resin release agents and other types of release agents. When demolding the template, the action mechanism of these release agents includes chemical action and physical lubrication. The chemical action is that the organic acid in the release agent can react with the alkaline substance on the surface of the template to form a film that is not easy to adhere, thereby reducing the adhesion between the concrete and the template and achieving the demolding effect; the physical lubrication effect is that the release agent can make the concrete surface smoother, reduce the contact area between the template and the concrete surface, thereby reducing friction and facilitating demolding.
[0032] Since both the 3D printed concrete formwork and the cast-in-place wall are made of concrete, the adhesion of the common release agent to the formwork and the cast-in-place wall is the same when a chemical reaction occurs. In addition, the 3D printed concrete has a porous structure, and the applied release agent will penetrate into the formwork, making it difficult to work. This causes the new and old concrete to bond when the concrete formwork is demolded, which makes demolding difficult, seriously affecting the turnover and use of the formwork. In addition, the 3D printed turnover formwork has the same problem as the common turnover formwork such as plastic formwork and wooden formwork, that is, the formwork is prone to bumps and scratches during transportation and turnover, resulting in missing edges of the formwork, which greatly reduces the turnover of the formwork, which further limits the turnover of the 3D printed formwork.
[0033] The protective coating provided by the present invention is helpful to alleviate the above situation. The developed protective coating is a polyurethane composite reinforced coating. After being applied to the template surface, it can react with the water molecules on the template surface to form a polyester acid compound, which penetrates into the micropores on the concrete surface and is tightly connected to the concrete template surface by molecular bonds. The water molecules on the interface-forming coating surface are continuously reduced and are tightly accumulated on the template surface and pores. At the same time, Ca(OH)2 generated by cement hydration in the template reacts with the carbamate groups in the polymer to generate carbamate metal salts, which are tightly connected to the polymer by ionic bonds to form a connected membrane structure with a certain thickness. The film is tightly connected to the pores on the template surface and penetrates each other. The product and the aggregate are mutually bonded to form a dense coating film tightly connected to the template. The micropowder added to the coating can well fill the pores on the material surface caused by the production method of concrete printing, increase the hydration reaction sites, facilitate the connection between the coating film and the template, form a template connection reinforcement layer, further enhance the surface hardness of the template, and prevent the template from being damaged during transportation and demoulding. After the reaction on the formwork surface is completed, due to the intermolecular force and the addition of lubricating components, the unreacted macromolecular polymers in the coating gather outward and connect with each other to form a smooth and dense polymer layer, reducing the direct contact between the concrete surface and the mold, reducing adhesion, and forming a demolding layer that is more conducive to demolding. In the case of cast-in-place walls, since the reaction in the coating has been completed, it is difficult for hydration reaction to occur again. Therefore, the connection strength between the interface layer and the formwork is greater than the connection strength with the wall. During demolding, the interface between the interface layer and the wall is a weak interface, which is easily damaged, making it easier to demold. In addition, the membrane structure generated by the reaction can prevent water molecules from entering the interior of the formwork, causing the formwork performance to decline, thereby avoiding affecting its turnover times and the quality of the formed wall.
[0034] 3. Beneficial effects
[0035] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects:
[0036] (1) The protective coating for the recyclable formwork of the present invention can generate a dense membrane structure near the concrete base, effectively improve the hardness of the formwork surface, and prevent the formwork from being damaged during transportation and demolding. A dense and smooth polymer membrane structure will be generated on the outside, reducing the direct contact between the concrete surface and the mold, reducing the adhesion and the bonding strength of the interface between the new and old concrete, and helping to reduce the friction between the concrete and the formwork, so that the wall can be demolded smoothly without damaging the formwork surface. The realization of this dual function makes the composite coating have a wide range of application prospects in the fields of construction and engineering, and can realize the recyclable use of 3D printed formwork. The coating is also applicable to other types such as wooden formwork and plastic formwork, further increasing the turnover number of the formwork.
[0037] (2) In conventional technology, when demolding, mold release agents are directly applied to the surface of the turnover formwork, such as wooden formwork and steel formwork. Vibration demolding is used to promote the separation of the formwork and the wall, and a crowbar is used to pry the edge of the formwork until the formwork is completely separated from the wall. This will cause the surface finish of the formwork to decrease or the surface to be damaged, affecting the subsequent use of the formwork. However, the protective treatment method of the turnover formwork of the present invention can form a membrane structure with a certain thickness on the surface of the formwork, which will not damage the surface of the formwork during demolding, thereby increasing the turnover times of the formwork.
[0038] (3) The protective treatment method of the turnover formwork of the present invention can make the surface of the formwork hydrophobic, thereby preventing moisture from entering the interior of the formwork during use, thereby reducing the performance of the formwork and affecting the service life of the formwork. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 This is a schematic diagram of the structure of the wedge-shaped protrusion on the inner side of the template in an embodiment of the present invention;
[0040] Figure 2 is a process flow chart of the protection treatment method in an embodiment of the present invention;
[0041] Figure 3 This is a schematic diagram of multi-level protection of the template surface in an embodiment of the present invention;
[0042] Figure 4 This is a schematic diagram of the analysis of the action mechanism of the protective coating in an embodiment of the present invention;
[0043] Figure 5 It is a schematic diagram of the wall after the template surface treatment and demoulding in the embodiment. DETAILED DESCRIPTION
[0044] In order to further understand the content of the present invention, the present invention is described in detail in conjunction with the accompanying drawings.
[0045] In the description of the present invention, it should be noted that the terms "center", "upper", "lower", "left", "right", "vertical", "horizontal", "inner", "outer", etc., indicating the orientation or positional relationship, are based on the orientation or positional relationship shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first", "second", and "third" are used for descriptive purposes only, and cannot be understood as indicating or implying relative importance.
[0046] The present invention will be further described below in conjunction with the embodiments.
[0047] Example 1
[0048] Combination Figure 1-Figure 5As shown, the protective coating for the recyclable template provided in this embodiment can be called a polyurethane composite reinforced coating, which is made by mixing component A and component B, wherein the main materials used in component A are nano-alumina and nano-silicon carbide powder, and a small amount of rare earth oxide Er2O3 is added, epoxy resin is used as the matrix, and a dispersant is added, the dispersant is sodium polyacrylate, and the main material of component B is polyether polyol, and micropowder, plasticizer, curing agent, coagulant and auxiliary agent are added, the plasticizer is ditoluene phosphate, the curing agent is ethylene triamine, the main component of the coagulant is calcium aluminate, and the auxiliary agent is non-tar asphalt. Specifically, the polyurethane composite reinforced coating in this embodiment includes: 18 parts by mass of nano-alumina; 15 parts by mass of nano-silicon carbide powder; 1 part by mass of rare earth oxide; 58 parts by mass of epoxy resin; 0.6 parts by mass of dispersant; 72 parts by mass of polyether polyol; 5 parts by mass of micropowder; 2 parts by mass of plasticizer; 1.0 parts by mass of curing agent; 2 parts by mass of coagulant; 8 parts by mass of auxiliary agent.
[0049] This embodiment also provides a multi-level protective treatment method for a recyclable template, that is, spraying the above-mentioned protective coating. Specifically, after the template is completed, the template surface is first cleaned and a layer of water-based primer is applied on the template surface; then the above-mentioned protective coating is sprayed on the template surface.
[0050] Taking the 3D printing template scenario as an example, after the template is printed, the inner surface of the template can be smoothed to prevent the 3D printing strips from affecting the flatness of the wall. After printing, cover the surface of the template with plastic film and maintain it at room temperature for seven days. After the template hardens, use a polishing machine to grind and cut the inner surface of the template again, and use intelligent CNC cutting equipment to cut the edges of the vertical strips with decorative effects on the inside of the template, so that the inner protrusion changes from a vertical protrusion to a wedge-shaped protrusion. The chamfer angle can be set in advance to an inclination of 15° to 80°, and a CNC cutting machine can be used for precise cutting to prevent the material interlocking between the newly poured wall and the 3D printed concrete template during wall pouring, resulting in difficulty in demolding. Then clean the surface of the 3D printed concrete template, and use a flexible brush to clean the cement residue on the inner and outer surfaces of the template to prevent affecting the adhesion of the interface agent and hardener on the surface. Then apply a layer of water-based primer on the surface of the template to play a role in preliminarily closing the gaps on the surface of the template; the water-based primer used in this embodiment can adopt a variety of water-based primer products currently common in the industry on the market, and its basic components are resin, additional filler, leveling agent and dispersant. The resin can be one or more of acrylic resin, polyurethane resin, and epoxy resin. The filler can be silicate and quartz sand. The leveling agent is an organosilicon leveling agent, and the main component of the dispersant is polyvinyl alcohol, etc.; this is a conventional technical product on the market and will not be repeated. After the water-based primer is applied, a low-temperature plasma generator is used to roughen the surface of the template to enhance the adhesion of subsequent coatings.
[0051] Specially, after the template surface is roughened, the template surface is continuously sprayed with polyurethane composite reinforced coating in this embodiment, and a low-pressure spray gun can be used to evenly spray on the template surface so that the reinforced coating completely covers the template surface. The coating of the reinforced coating is three times, with an interval of 3 hours and a coating thickness of 0.03 mm each time; carboxymethyl cellulose is added as a viscosity regulator during spraying, and the amount is 3% of the total weight of the coating. During spraying, the coating is atomized by compressed air, and then sprayed in a mist form, uniformly covering the outer surface of the template. To achieve a better atomization effect, the spray gun power is above 20kw. After the interface layer is formed into a film, before the wall is poured, a roller coating or a flexible brush is used to continuously and evenly brush the engine oil on the interface layer of the inner surface of the template as a lubricating isolation layer, so that the engine oil completely covers the interface layer, plays a lubricating and isolating role, and is convenient for subsequent template demoulding. Finally, cure it for three days at 20℃ ~ 30℃. During the curing process, ensure that the coating area is well ventilated and try to avoid dust, oil and other pollutants from contacting the coating to avoid affecting the final effect. After the coating is cured, it is easy to demold the template and can significantly improve the surface hardness and wear resistance of the template.
[0052] Example 2
[0053] The protective treatment method for the recyclable template provided in this embodiment is basically the same as that in embodiment 1, except that the polyurethane composite reinforced coating used in this embodiment includes: 22 parts by mass of nano-alumina; 21 parts by mass of nano-silicon carbide powder; 2 parts by mass of rare earth oxide; 62 parts by mass of epoxy resin; 0.5 parts by mass of dispersant; 75 parts by mass of polyether polyol; 7 parts by mass of micro powder; 4 parts by mass of plasticizer; 1.5 parts by mass of curing agent; 2 parts by mass of accelerator; 12 parts by mass of auxiliary agent. The protective coating is sprayed four times, each time with an interval of 3.5 hours, each spraying thickness of 0.04 mm, and the amount of carboxymethyl cellulose added during spraying is 2.5% of the total weight of the coating.
[0054] Example 3
[0055] The protective treatment method for the recyclable template provided in this embodiment is basically the same as that in embodiment 1, except that the polyurethane composite reinforced coating used in this embodiment includes: 26 parts by mass of nano-alumina; 21 parts by mass of nano-silicon carbide powder; 3 parts by mass of rare earth oxide; 65 parts by mass of epoxy resin; 0.9 parts by mass of dispersant; 70 parts by mass of polyether polyol; 5 parts by mass of micro powder; 5 parts by mass of plasticizer; 1.6 parts by mass of curing agent; 3 parts by mass of accelerator; 8 parts by mass of auxiliary agent. The protective coating is sprayed five times, each time with an interval of 3 hours, and each spray thickness is 0.035 mm. The amount of carboxymethyl cellulose added during spraying is 2.6% of the total weight of the coating.
[0056] Example 4
[0057] The protective treatment method for the turnover formwork provided in this embodiment is basically the same as that in Embodiment 1, except that the polyurethane composite reinforced coating used in this embodiment includes: 19 parts by mass of nano-alumina; 13 parts by mass of nano-silicon carbide powder; 1 part by mass of rare earth oxide; 60 parts by mass of epoxy resin; 0.5 parts by mass of dispersant; 73 parts by mass of polyether polyol; 6 parts by mass of micropowder; 2 parts by mass of plasticizer; 0.9 parts by mass of curing agent; 2 parts by mass of accelerator; and 12 parts by mass of additive.
[0058] Comparative Example 1
[0059] The protective treatment method for a recyclable template provided in this comparative example is basically the same as that in the above-mentioned Example 1, except that the protective coating used in this comparative example only contains component A, that is, it only contains: the main materials are nano-alumina and nano-silicon carbide powder, and a small amount of rare earth oxide Er2O3 is added, epoxy resin is used as the matrix, and a dispersant is added, the dispersant is sodium polyacrylate, and the content of each component is the same as that in the above-mentioned Example 1.
[0060] Comparative Example 2
[0061] The protective treatment method for the turnover formwork provided in this comparative example is basically the same as the above embodiment, except that the protective coating used in this comparative example only contains component B, namely: the main material is polyether polyol, with additional micropowder, plasticizer, curing agent, accelerator and auxiliary agent, the plasticizer is ditolyl phosphate, the curing agent is ethylenetriamine, the main component of the accelerator is calcium aluminate, and the auxiliary agent is non-tar asphalt. The content of each component is the same as in the above embodiment 1.
[0062] Comparative Example 3
[0063] The protective treatment method for the turnable formwork provided in this comparative example is basically the same as that in the above-mentioned embodiment, except that the protective coating in the embodiment is not used in this comparative example, but the engine oil commonly used in formwork engineering is selected as the release agent as the interface agent on the inner surface of the formwork.
[0064] In practice, the test method of the bonding performance of concrete formwork and wall is used to test the effect of surface agent on demoulding performance. The following steps are followed:
[0065] 1. Preparation of new and old concrete specimens. The bonding performance between the formwork and the wall can be approximated to the bonding performance between the new and old concrete. The specimens were made using a 100mm×100mm×100mm plastic mold. The specimens were made in two parts. First, 50mm was poured as the old concrete. The grooving method was used at the connection interface to simulate the different roughness of the actual situation. The roughness of the bonding interface was controlled and evaluated using the roughness index. The old concrete was surface treated after 7 days of curing. After the treatment, new concrete was poured. After the vibration was completed, it was covered with plastic film and allowed to stand for curing.
[0066] 2. Use the splitting tensile test to test the bond strength of the interface between the new and old concrete. The experiment is carried out according to the provisions of the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" (GB / T50081-2019). The specific loading process is as follows: ① Before the specimen loading test, clean the upper and lower loading plates of the press. Draw a parallel line between the upper and lower surfaces of the new and old concrete bonding specimens to determine the cross-section loading position. ② Place the specimen in the splitting fixture, first remove the upper steel pad, place the plywood pad in the middle of the bottom of the pad, hold up the bottom of the specimen with both hands, adjust the specimen to the center, and then put the upper steel pad back in. Place the specimen with the fixture in the middle of the lower plate of the press, and ensure that the upper and lower pads are aligned with the lines drawn on the surface of the specimen. ③ Start the pressure tester. When loading, make sure that the fixture can fit the upper and lower plates of the press, and control the loading speed to 0.04~0.08MPa / s. The loading speed must be continuous and uniform to avoid large errors. Record the load when the specimen fails, and calculate the splitting tensile strength of the new and old concrete bonding specimens.
[0067] In practice, the test method of template surface hardness is used to test the effect of nano-ceramic coating on template surface hardness, and the following steps are followed:
[0068] The outer surface hardness of each embodiment was measured using a Shore hardness tester. The hardness tester pointer was reset to zero before use, and then the needle was pressed vertically against the sample surface at a uniform speed until the end face of the hardness tester needle was completely in contact with the surface of the sample to be tested. The tested value on the hardness tester dial was recorded, and the average value of three different positions was taken as the hardness of the template surface.
[0069] The splitting tensile strength of the connection surface of each case is shown in Table 1 below, and the surface hardness of each template is shown in Table 2 below.
[0070] Table 1: Splitting tensile strength of each template connection surface
[0071]
[0072] Table 2: Surface hardness of each template
[0073] Rockwell hardness value Example 1 87 Example 2 91 Example 3 92 Example 4 89 Comparative Example 1 63 Comparative Example 2 77 Comparative Example 3 52
[0074] It can be seen from Table 1 that the use of polyurethane composite coating can significantly reduce the interfacial bonding strength of the template facing area and the non-facing area. Compared with adding only component A, the splitting tensile strength of the mixed coating is reduced by 100% and 76%, respectively, compared with adding only component B, the splitting tensile strength is reduced by 100% and 80%, respectively, compared with using conventional release agents, the splitting tensile strength is reduced by 100% and 86%, respectively, indicating that the composite coating has good applicability for 3D printing turnover template demolding, and can achieve smooth demolding of the template.
[0075] It can be seen from Table 2 that the use of the polyurethane composite coating in the embodiment of the present invention can significantly improve the surface hardness of the template. Compared with adding only component A, the surface hardness is increased by 39%, compared with adding only component B, the surface hardness is increased by 15%, and compared with using a conventional release agent, the surface hardness is increased by 69%.
[0076] The above is a schematic description of the present invention and its implementation mode, which is not restrictive and is only one of the implementation modes of the present invention, and is not actually limited thereto. Therefore, if a person skilled in the art is inspired by it and, without departing from the purpose of the invention, designs a structure and an implementation mode similar to the technical solution without creativity, they shall all fall within the protection scope of the present invention.
Claims
1. The protective coating of the turnover formwork is characterized by: The composition comprises the following components in parts by weight: Nano-alumina: 18-26 parts by mass, Nano silicon carbide powder: 13-21 parts by mass, Rare earth oxide: 1 to 3 parts by mass, Epoxy resin: 58-65 parts by mass, Dispersant: 0.5-0.9 parts by mass, Polyether polyol: 70-75 parts by mass, Micro powder: 5-7 parts by weight, Plasticizer: 2 to 5 parts by weight, Curing agent: 0.9 to 1.6 parts by mass, Coagulant: 2-3 parts by weight, Additives: 8 to 12 parts by weight.
2. The protective coating for the recyclable formwork according to claim 1 is characterized in that: The rare earth oxide is Er2O3; or / and, the dispersant is sodium polyacrylate; or / and, the plasticizer is ditolyl phosphate; or / and, the curing agent is ethylenetriamine; or / and, the coagulant is calcium aluminate; or / and, the auxiliary agent is non-tar asphalt.
3. The protective coating for the recyclable formwork according to claim 1 is characterized in that: The average particle size of nano-alumina is 60-70nm; or / and, the average particle size of nano-silicon carbide is 45-55nm; or / and, the density of epoxy resin is 1.1-1.3g / cm 3 , viscosity is 7500-8000 Pa·s; or / and, the micropowder is silicon carbide powder, the average particle size of the micropowder is 25-30 nm, and the specific surface area is 80-100 m 2 / g, density is 3.6~3.9g / cm 3 .
4. A protective treatment method for a turnaround formwork, characterized in that: Spray the protective coating as described in any one of claims 1 to 3 on the surface of the template.
5. The protective treatment method for the turnable formwork according to claim 4 is characterized in that: The process includes: S1. Make the concrete formwork, clean the formwork surface, and apply a layer of water-based primer on the formwork surface; S2. Spray protective coating on the template surface.
6. The protective treatment method for the turnable formwork according to claim 5 is characterized in that: In step S2, carboxymethyl cellulose is added as a viscosity modifier when the protective coating is sprayed, and the amount of carboxymethyl cellulose used is 2.5-3% of the total weight of the coating.
7. The protective treatment method for the turnable formwork according to claim 5 is characterized in that: The protective coating in step S2 is sprayed no less than three times, with an interval of no less than 3 hours, and the thickness of each spraying is no less than 0.03 mm.
8. The protective treatment method for the turnable formwork according to claim 5 is characterized in that: In step S1, after the template is completed, the edges of the vertical strips on the inner side of the template are cut to form a wedge-shaped protrusion on the inner side, and then the surface of the template is cleaned.
9. The protective treatment method for the turnable formwork according to claim 5 is characterized in that: In step S1, after the water-based primer is applied to the surface of the template, the surface of the template is roughened and then the protective coating is sprayed.
10. The protective treatment method for a turnable formwork according to any one of claims 5 to 9, characterized in that: After the spraying in step S2 is completed, continue to brush the lubricating isolation layer on the surface of the template: after the interface layer is formed into a film, before pouring the wall, brush the engine oil evenly on the interface layer on the inner surface of the template, and the engine oil completely covers the interface layer.
Citation Information
Patent Citations
Concrete water-based demolding protection emulsion and application thereof
CN113025173A
Template paint for environment-friendly low-surface-energy aluminum alloy template and preparation method of template paint
CN116042075A
